Randomized Trial of a Health Coaching Intervention to Enhance Retention in Care: California Collaborative Treatment Group 594 - Corado, Katya (AIDS Behav, 2018)
Poor linkage, engagement and retention remain significant barriers in achieving HIV treatment goals in the US. HIV-infected persons entering or re-entering care across three Southern California academic HIV clinics, were randomized (1:1) to an Active, Linkage, Engagement, Retention and Treatment (ALERT) specialist for outreach and health coaching, or standard of care (SOC). The primary outcome of time to loss to follow up (LTFU) was compared using Cox proportional hazards regression modeling. No differences in the median time to LTFU (81.7 for ALERT versus 93.6 weeks for SOC; HR 1.27; p = 0.40), or time to ART initiation was observed (N = 116). Although, ALERT participants demonstrated worsening depressive symptomatology from baseline to week 48 compared to SOC (p = 0.02). The ALERT intervention did not improve engagement and retention in HIV care over SOC. Further studies are needed to determine how best to apply resources to improve retention and engagement.